Climate change in Central and South America: Recent trends, future projections, and impacts on regional agriculture - Marengo, JA; Chou SC; Torres, R.R.; Giarolla, A; Alves, L.M.; Lyra, A (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This report investigates the climate of two target regions of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS): Central and South America (CA and SA, respectively). The report assesses the implications of climate change for agriculture, with a particular focus on those aspects of climate change that will have greatest impact on the crops currently grown in each region. The study investigated the ability of General Circulation Models (GCMs) and downscaled climate change scenarios to reproduce already observed climates, to establish the reliability of future climate projections, as well as projections of how associated crops might grow under future conditions.